Corporate Governance Dan Profitabilitas Perusahaan Publik Di Indonesia - Eka Febiyanti Samhudi; Hersugondo Hersugondo (Jurnal Manajemen dan Keuangan, 2022)
This study examines the relationship between internal corporate governance mechanisms consisting of the size of the board of directors, the board of commissioners, the proportion of independent commissioners, institutional ownership and managerial ownership on profitability as measured using the return on asset (ROA) ratio and using control variables, namely sales growth and risk. business. A total of 807 companies listed on the Indonesia Stock Exchange during 2015 to 2020 were included in the population in this study. After using purposive sampling technique, 300 companies from various sectors were used as research samples. The data processing technique used is multiple regression analysis using SPSS version 23 software. Several tests were carried out such as Pearson Correlation, F Test, Coefficient of Determination and T Test to see the relationship and influence between variables. This study found a positive and significant relationship between the size of the board of directors, the size of the board of commissioners and managerial ownership on return on assets (ROA), meaning that the increase in the return on company assets is influenced by these three variables. The proportion of independent commissioners and institutional ownership does not have a significant effect on return on assets because it is based on the results of the t test with a significance value > 0.05. The sales growth control variable has a positive and significant effect on ROA while business risk has a negative and significant relationship with ROA. This research has important implications for policy makers within the company as well as for researchers in the same field.